1994
DOI: 10.1017/s0813483900005039
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a General-Practice-Based Physical Activity Intervention on Patient Physical Activity Status

Abstract: Physical inactivity is a risk factor for a number of chronic diseases, including cardiovascular disease. Interventions designed to reduce the prevalence of physical inactivity have focused primarily on either adoption of physical activity or noncompliance and relapse, and no interventions have been reported which cover adoption, compliance, maintenance, and relapse, particularly within the clinical setting. TheFresh Startprogram, a multiple risk factor intervention program for the reduction of cardiovascular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…The Change of Heart Study is a randomized controlled trial that compares brief behavioral counseling with usual health promotion advice among patients at increased risk of coronary heart disease in a primary care setting, 7 where there is limited evidence regarding the effects of stage-oriented programs. [8][9][10] The behavioral and biological risk factor results of this study, which have been described elsewhere, show greater reductions in fat intake and the number of cigarettes smoked and greater increases in physical activity in the behavioral intervention group than in the control group at 4 and 12 months. 11 In this article, we present stage of change outcomes in the study and address (1) whether behavioral intervention was more effective than normal practice in achieving the target stage (action/maintenance), (2) whether the likelihood of achieving the target stage for each behavior varied with initial stage, and (3) whether any advantage of behavioral intervention was equally evident for patients at different stages of readiness at baseline.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…The Change of Heart Study is a randomized controlled trial that compares brief behavioral counseling with usual health promotion advice among patients at increased risk of coronary heart disease in a primary care setting, 7 where there is limited evidence regarding the effects of stage-oriented programs. [8][9][10] The behavioral and biological risk factor results of this study, which have been described elsewhere, show greater reductions in fat intake and the number of cigarettes smoked and greater increases in physical activity in the behavioral intervention group than in the control group at 4 and 12 months. 11 In this article, we present stage of change outcomes in the study and address (1) whether behavioral intervention was more effective than normal practice in achieving the target stage (action/maintenance), (2) whether the likelihood of achieving the target stage for each behavior varied with initial stage, and (3) whether any advantage of behavioral intervention was equally evident for patients at different stages of readiness at baseline.…”
supporting
confidence: 68%
“…One study involving short interventions of 3 to 5 minutes coupled with written information targeted dietary fat consumption, 20 as did a nonrandomized study of physical activity counseling by physicians. 9 A more extensive trial of physical activity counseling by general practitioners in Australia did not demonstrate any advantage of stage-based programs over routine care, 8 while a recent study of tailored physical activity counseling also showed no differences between intervention subjects and controls in activity levels at 6 weeks or 8 months. 21 None of these investigations focused on patients at increased risk for cardiovascular disease, but it can be argued that such patients may be more motivated to change and more likely to receive benefit from lifestyle intervention.…”
Section: Discussionmentioning
confidence: 95%
“…but "which TTM based activity promotion interventions are effective?". Only one of the studies reviewed 12 attempted to compare different methods of delivering TTM based interventions. More comparative studies of TTM based interventions of known effectiveness should be made.…”
Section: Discussionmentioning
confidence: 99%
“…As with the general population, individuals with diabetes and CVD are advised to undertake 30 min or more of moderate physical activity during their leisure time on 5 or more days of the week (Australian Government Department of Health and Ageing, 2005). Numerous interventions to improve physical activity levels (Dishman & Buckworth, 1996;Hillsdon, Foster, & Thorogood, 2005;Kahn et al, 2002;MĂĽller-Riemenschneider, Reinhold, Nocon, & Willich, 2008), including some specifically aimed at people diagnosed with diabetes or CVD (Furber et al, 2008;Gleeson-Kreig, 2006;Graham-Clarke & Oldenburg, 1994;Richardson et al, 2007;Steptoe et al, 1999;Wing, Vendetti, Jakicic, Polley, & Lang, 1998), have been developed using a number of different approaches (e.g., pedometer wearing/diary recording, behavior therapy, self-monitoring) to encourage positive changes in people's physical activity levels. However, although some improvements in people's physical activity levels have been observed (Page, Harnden, Cook, Turner, 1992;Simons-Morton, Calfas, Oldenburg, & Burton, 1998;Steptoe et al, 1999;Wing et al, 1998), they have typically been, at best, only modest and often not maintained.…”
Section: Original Researchmentioning
confidence: 99%